Effect of foliar spraying of micronutrients on growth and yield of potato (Solanum tuberosum) (Current Horticulture, 2024)
The experiment was conducted to find out the effect of foliar spraying of micronutrient on growth and yield of potato (Solanum tuberosum L.) during 2019-20 at Vegetable Research Farm, Department of Horticulture, BHU, Varanasi. The experiment was laid out in a randomised block design with 3 replications having 9 treatments. The treatments were T1 ( control), T2 (B-20 (boron) @ 0.06%), T3(B-20 (boron) @ 0.09%), T4(zinc sulphate @ 0.03%), T5 (zinc sulphate @ 0.05%), T6 (B-20 (boron) @ 0.06% + zinc sulphate @ 0.03%) T7 (B-20 (boron) @ 0.06% + zinc sulphate @ 0.05%), T8 (B-20 (boron) @ 0.09% + zinc sulphate @ 0.03%) and T9 (B-20 (boron) @ 0.09% + zinc sulphate @ 0.05%). T9 (B-20 (boron) @ 0.09% + zinc sulphate @ 0.05%) was found to be the best for all the growth and yield traits except for number of leaves in that T3 (B-20 (boron) @ 0.09%) was recorded with highest value, for the rest trait followed by T7 (B-20 (boron) @ 0.06% + zinc sulphate @ 0.05%) and T8 (B-20 (boron) @ 0.09% + zinc sulphate @ 0.03%), while the least value was observed in T1 (control) that was sprayed with water.
Keywords: Boron; Growth; Zinc sulphate; Micronutrients; Treatment; Yield